2011
DOI: 10.1007/s00784-011-0581-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single-dose amoxicillin on rat incisor odontogenesis: a morphological study

Abstract: The effect of exposure to amoxicillin on tooth development remains to be elucidated. The purpose of this study was to investigate the effect of amoxicillin on rat incisor odontogenesis. Male Wistar rats weighing approximately 100 g were given a single intraperitoneal injection of 3.0 g/kg body weight amoxicillin. One week after injection, the rats were fixed, and the lower incisors were demineralized and prepared into paraffin sections for light microscopy (LM) and immunohistochemistry. Undemineralized samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…Amoxicillin seems to be the only antibiotic, of which potential adverse effects on tooth development have been reported. 17,18 The situation in the second patient is even more obscure. This girl ingested a corticosteroid with mother's milk during 2 months of breast-feeding immediately after birth.…”
Section: Discussionmentioning
confidence: 98%
“…Amoxicillin seems to be the only antibiotic, of which potential adverse effects on tooth development have been reported. 17,18 The situation in the second patient is even more obscure. This girl ingested a corticosteroid with mother's milk during 2 months of breast-feeding immediately after birth.…”
Section: Discussionmentioning
confidence: 98%
“…12 Amoxicillin, in turn, has been found to affect amelogenesis in cultured mouse molars 6 and dentin mineralization in rat incisors in vivo. 13 The severity of the defects caused by amoxicillin 6 or fluoride 10 is dose dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical conditions, possibly other factors present protective hole against erosion, such as the presence of acquired pellicle [37].In the present study, with the limitations of an in vitro study, it was tried to simulates some clinical parameters, for example, the time of contact with amoxicillin was similar to the real condition in order to simulate the time of clearance of this antibiotic in the mouth. Even thought, in vitro models as present limitations, such as the impossibility to completely simulate the complex intraoral conditions; they cannot simulate solid surface area/solution ratios because the different oral surfaces are bathed in different volumes and source combinations of saliva; they cannot mimic topical use and clearance of substances from the oral cavity and, in many times, cannot simulate the tooth brushing as it happens in clinical environment [15]. This mentioned limitations must be highlighted when in vitro studies are performed, in these cases, the conduction of in situ studies are suggested to minimize the limitations of in vitro protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The palatability of these medicines is increased with the addition of sugars such as sucrose, glucose or fructose to foster patients' acceptability and thus compliance [12,13]. Furthermore, the pH is formulated to optimize their efficacy, and, usually acidic preparations are often necessary for drug dispersion [5,14,15]. Thus, liquid oral medicines may act as extrinsic agents causing biodegradation of resin-based materials, especially if consumed frequently [5].…”
Section: Introductionmentioning
confidence: 99%